EXPRESS: Beyond Profits: Does Mimicry Lead to Greater Social Good? - Liu, Guowei; Sun, Jiong; Zhang, Jianxiong (Production and Operations Management, 2026)
This paper investigates how dual-purpose firms—organizations that pursue both profit and social objectives—strategically design their product lines in markets where traditional profit-maximizing firms may imitate their behavior. We find that consumer heterogeneity plays a non-monotonic effect on the ability of dual-purpose firms to differentiate themselves from profit maximizers, which, in turn, influences firms’ product offering strategies and consumer welfare. When consumer heterogeneity is moderate, dual-purpose firms can credibly signal their social commitment without incurring additional signaling costs, leading to costless separation and efficient product differentiation. However, when consumer heterogeneity is either sufficiently low or sufficiently high, dual-purpose firms may exert additional efforts to provide consumers with their preferred (efficient) qualities or come closely approaching them, effectively distinguishing themselves from profit maximizers. This results in a positive surplus even for low-valuation consumers, which further increases as consumer heterogeneity becomes even lower or higher. The driving force is the stronger incentive for profit maximizers to mimic dual-purpose firms. Yet, these signaling efforts come at a cost, diminishing the firm’s overall utility and making differentiation harder to sustain in highly prosocial markets. Our findings also highlight that the societal value of publicly disclosing a firm’s social orientation is context-dependent. In some cases, mandated transparency may actually diminish consumer welfare relative to market-based self-signaling mechanisms. These insights offer strategic guidance for dual-purpose firms and inform policy decisions on when to support disclosure versus letting market forces facilitate differentiation.